2012
DOI: 10.1063/1.3692297
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic heat transport in nanoconfined polyamide-6,6 oligomers: Atomistic reverse nonequilibrium molecular dynamics simulation

Abstract: While polymers are known as thermal insulators, recent studies show that stretched single chains of polymers have a very high thermal conductivity. In this work, our new simulation scheme for simulation of heat flow in nanoconfined fluids [H. Eslami, L. Mohammadzadeh, and N. Mehdipour, J. Chem. Phys. 135, 064703 (2011)] is employed to study the effect of chain ordering (stretching) on the rate of heat transfer in polyamide-6,6 nanoconfined between graphene surfaces. Our results for the heat flow in the paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 42 publications
3
25
1
1
Order By: Relevance
“…The heat transfer channel in in-plane direction was through long polymer chain linkages and the heat transfer channel in through-plane direction was between polymer chain linkages. Additionally, atomistic reverse nonequilibrium molecular dynamics simulation (ARNMDS) also support the above experimental results, which revealed that well-organized polymer layers between the confined surfaces could show an anisotropic heat conduction and the heat conduction in the direction parallel to the surfaces was much higher than that in the perpendicular direction [29].…”
Section: Thermal Diffusivity Of Hot-pressed Pg Compositesmentioning
confidence: 54%
“…The heat transfer channel in in-plane direction was through long polymer chain linkages and the heat transfer channel in through-plane direction was between polymer chain linkages. Additionally, atomistic reverse nonequilibrium molecular dynamics simulation (ARNMDS) also support the above experimental results, which revealed that well-organized polymer layers between the confined surfaces could show an anisotropic heat conduction and the heat conduction in the direction parallel to the surfaces was much higher than that in the perpendicular direction [29].…”
Section: Thermal Diffusivity Of Hot-pressed Pg Compositesmentioning
confidence: 54%
“…This may be due to the ultralow thermal conductivity of the polymer (~0.1 W/m·K) compared to that of graphene (>100 W/m·K), transforming the ballistic heat transfer in graphene to the diffusive heat transfer in polymers [76,77]. Moreover, a number of theoretical studies have demonstrated that the interfacial thermal resistance (often known as the Kapitza resistance) between graphene and polymer also lowers the thermal conductivity of the composite films [78][79][80][81].…”
Section: Hybridization With Other Componentsmentioning
confidence: 99%
“…Meng et al [8] prepared carbon nanotube (CNT)-filled perfluoroalkoxy (PFA) films using a blade-coating method to improve the electro-thermal properties; Eslami et al [9] analyzed anisotropic heat transport in nanoconfined polyamides and proved that the interlayer spacing and porosity had very important influences on the heat conductivity; Cai et al [10] synthesized a PTFE (polytetrafluoroethylene)–graphene composite through compression molding and free sintering and investigated the range of thermal conductivity with different graphene contents. Rooyen [11] clarified the effects of the addition of graphene and the preparation methods on the physical properties of the grapheme-PTFE composites; Tanaka et al [12] investigated the friction and wear properties of two kinds of PTFE composites filled with CNTs and graphene, respectively, and they thought the lamellar structure of the graphene enhanced the self-lubricity of the composite due to the sliding between the graphene sheets; Takeichi [13] and Sidebottom [14] also executed relative research on the friction properties of carbon-PTFE and PFA-alumina composites.…”
Section: Introductionmentioning
confidence: 99%